The Homology and Cohomology Groups of H3 - Majumdar, Subrata; Sultana, Quazi Selina (GANIT: Journal of Bangladesh Mathematical Society, 2011)
A free resolution of Z for the integral group ring of the three-dimensional Heisenberg group H3 has been constructed by extending Lyndon’s partial resolution. The integral homology and cohomology have been calculated from there. AMS Classification: 18G, 20J. Key words: Fox derivatives; free resolution. GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 29 (2009) 139-146 DOI: http://dx.doi.org/10.3329/ganit.v29i0.8523